Psychosocial processes in the affective bonding of university students of Information Systems Engineering at the National University, Costa Rica (Costa Rican Journal of Guidance & Counseling, 2024)
Objective: The manuscript analyzed the psychosocial processes inherent in the couple dynamics of students enrolled in the Information Systems Engineering program at the Universidad Nacional, Costa Rica.Methodology: A qualitative methodology of a narrative nature was adopted, and the research covered five participating couples. For data collection, semi-structured interviews and the life history method were used during the year 2021, allowing a significant deepening in the subjects' personal experiences.Results: The analysis of the data revealed that communication between couples is characterized by a predominantly positive orientation, evidencing secure attachment patterns and a marked reciprocity in interpersonal attraction.Conclusions: The findings highlight the importance of promoting additional research in the field of counseling that delves into couple relationships, especially in specialized academic contexts, to strengthen the body of available knowledge that underpins affective dynamics in university settings.
Keywords: Interpersonal relationships; University student; Psychosocial processes; Interpersonal communication